Association between sleep quality and body weight status in adults: A narrative review - Yokanantini, M.; Ying, C.Y. (2021)
Introduction: Body weight status, viewed as a Body Mass Index (BMI), is a proven and accurate body fat status measure for general health designation. BMI acts as a predictive tool of disease; as BMI rises, so does some diseases' risk. A wide variety of negative health impacts of insufficient sleep, such as the risk of obesity, diabetes, cerebrovascular disorders, musculoskeletal diseases, and metabolic syndrome, have also been correlated. Obesity, particularly overweight among adults, is approaching epidemic proportions worldwide, while sleep quality has dramatically impacted both individuals and their society. Objective: This review aims to highlight the assessment of body weight status and sleep quality, summaries the recent literature, and provides an overview of the association between sleep quality and body weight status among the adult population. Methodology: Studies on sleep and BMI were reviewed, and findings were used to develop a link between sleep quality and body weight status. This paper offers a current review of the literature on the association between sleep quality and body weight status in adults. Results: This review discusses contradictory literature showing that shorter and longer sleep duration is associated with obesity. However, in most subjects with shorter sleep duration, there was a higher BMI trend than those who slept more. This is due to shorter sleep duration was correlated with enhanced ghrelin and decreased leptin. Low sleep quality was significantly correlated with severe obesity in male and female subgroups. Conclusion: There is an association between sleep quality and body weight status. More research is recommended to examine the impacts of lifestyle intervention on sleep quality improvement. Better health is associated with longer and sufficient duration of sleep. Therefore, it is of great significance to enhance the public awareness of their sleep quality on body weight status.